1995
DOI: 10.1111/j.1399-6576.1995.tb04202.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen tension‐associated changes on secondary immune response in halothane or isoflurane anesthetized mice

Abstract: The impact that reexposure to anesthetics delivered in 100% oxygen or in synthetic air (21% oxygen/79% nitrogen) has on the secondary humoral immune response to sheep red blood cells was studied. Mice were immunized twice with a 15-day interval and anesthetized immediately after each antigenic challenge with 1.5% halothane or 1.5% isoflurane for 40 min. Halothane in oxygen resulted in increased numbers of IgG-secreting cells (IgG-SC), while halothane in air depressed the response when compared to control mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…In response to anaesthetic exposure, humoral parameters, such as the number of immunoglobulin G secreting cells, are altered in animal studies [19,20]. Exposure to low concentrations of volatile anaesthetics seems to inhibit predominantly T-helper cell function [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to anaesthetic exposure, humoral parameters, such as the number of immunoglobulin G secreting cells, are altered in animal studies [19,20]. Exposure to low concentrations of volatile anaesthetics seems to inhibit predominantly T-helper cell function [11].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to low concentrations of volatile anaesthetics seems to inhibit predominantly T-helper cell function [11]. It has been reported that low concentrations of anaesthetics preferentially impair T cell activity, whereas higher concentrations also affect B cells [19,20]. This effect could be explained by impaired T-helper cell activity that adversely affects B cell activity.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, neither anesthetic induced dramatic changes of cell membrane plasticity or hypertrophy of the Golgi apparatus, nor did they produce any profound effect on the platelets. Isoflurane shares the halothane-anesthetic mechanism, but displays very low biotransformation and shows no immune response in the same model (Baden and Rice, 1990;Puig et al, 1995;Elena et al, 1997). It has a reduced tendency to cause perturbation of the cell membrane when compared with halothane (Koubi et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…activation. Halothane increases the antibody titre 8 , and, as sevoflurane does, it increases the primary and secondary responses 5,8,9,20,21,27 .…”
Section: Il-6mentioning
confidence: 99%
“…Thus, part of the effect of anaesthetics on the immune system would be due to its action on the well-known immunomodulatory effect of glucocorticoids 3 . Diverse in vitro experiments with human immune cells 4 , ex vivo [5][6][7] , in vivo [8][9][10] or animal models have been used to study the effect of anaesthetic drugs on the immune system. .…”
Section: Introductionmentioning
confidence: 99%